Capital Participation of PT Pelabuhan Indonesia (Persero) Merger on Ship Assets - Boy Robyanto; Serlly Waileruny (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This article aims to explain the status of ships under Pelindo's property rights, and what legal remedies Pelindo can take after the merger. This research is an empirical juridical legal research (non-doctrinal). The type of data used in this research is secondary data. This research uses three approaches, namely statute approach, case approach, and conceptual approach. Furthermore, related to data analysis, the data collected from the research results were then analyzed by the author in a descriptive-qualitative manner. The result of this study is that the merger carried out by PT Pelindo against PT Pelindo I, III, and IV has implications for the value of the company's assets that increase, this condition causes the inclusion of the company's authorized capital. The special thing that must be considered in this merger is about ship assets. Ship assets that have not been renamed, cannot be used in operational activities and the ship is not loaded with property rights and is suitable for operation. Therefore, the ship must be renamed in accordance with the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 39 of 2017 concerning Ship Registration and Nationality.